Adjuvant immunotherapy with nivolumab versus observation in completely resected Merkel cell carcinoma (ADMEC-O): disease-free survival results from a randomised, open-label, phase 2 trial - Becker, Jürgen C.; Ugurel, Selma; Leiter, Ulrike; Meier, Friedegund; Gutzmer, Ralf; Haferkamp, Sebastian; Zimmer, Lisa; Livingstone, Elisabeth; Eigentler, Thomas K; Hauschild, Axel; Kiecker, Felix; Hassel, Jessica C.; et al. (The lancet, 2023)
Background - Merkel cell carcinoma (MCC) is an immunogenic but aggressive skin cancer. Even after complete resection and radiation, relapse rates are high. PD-1 and PD-L1 checkpoint inhibitors showed clinical benefit in advanced MCC. We aimed to assess efficacy and safety of adjuvant immune checkpoint inhibition in completely resected MCC (ie, a setting without an established systemic standard-of-care treatment). - Methods - In this multicentre phase 2 trial, patients (any stage, Eastern Cooperative Oncology Group performance status 0-1) at 20 academic medical centres in Germany and the Netherlands with completely resected MCC lesions were randomly assigned 2:1 to receive nivolumab 480 mg every 4 weeks for 1 year, or observation, stratified by stage (American Joint Committee on Cancer stages 1-2 vs stages 3-4), age (<65 vs ≥65 years), and sex. Landmark disease-free survival (DFS) at 12 and 24 months was the primary endpoint, assessed in the intention-to-treat populations. Overall survival and safety were secondary endpoints. This planned interim analysis was triggered when the last-patient-in was followed up for more than 1 year. This study is registered with ClinicalTrials.gov (NCT02196961) and with the EU Clinical Trials Register (2013-000043-78). - Findings - Between Oct 1, 2014, and Aug 31, 2020, 179 patients were enrolled (116 [65%] stage 3-4, 122 [68%] ≥65 years, 111 [62%] male). Stratification factors (stage, age, sex) were balanced across the nivolumab (n=118) and internal control group (observation, n=61); adjuvant radiotherapy was more common in the control group. At a median follow-up of 24·3 months (IQR 19·2-33·4), median DFS was not reached (between-groups hazard ratio 0·58, 95% CI 0·30-1·12); DFS rates in the nivolumab group were 85% at 12 months and 84% at 24 months, and in the observation group were 77% at 12 months and 73% at 24 months. Overall survival results were not yet mature. Grade 3-4 adverse events occurred in 48 [42%] of 115 patients who received at least one dose of nivolumab and seven [11%] of 61 patients in the observation group. No treatment-related deaths were reported. - Interpretation - Adjuvant therapy with nivolumab resulted in an absolute risk reduction of 9% (1-year DFS) and 10% (2-year DFS). The present interim analysis of ADMEC-O might suggest clinical use of nivolumab in this area of unmet medical need. However, overall survival events rates, with ten events in the active treatment group and six events in the half-the-size observation group, are not mature enough to draw conclusions. The explorative data of our trial support the continuation of ongoing, randomised trials in this area. ADMEC-O suggests that adjuvant immunotherapy is clinically feasible in this area of unmet medical need. - Funding - Bristol Myers Squibb.